Heavy metals in the diet: unraveling the molecular pathways linked to neurodegenerative disease risk - GUEVARA RAMIREZ, ALEXANDRA PATRICIA; TAMAYO TRUJILLO, VICTOR RAFAEL; CADENA ULLAURI, SANTIAGO ANDRE; RUIZ POZO, VIVIANA ALEJANDRA; PAZ CRUZ, ELUIS ANDRES; Giuseppe Annunziata; Ludovica Verde; Evelyn Frias-Toral; SIMANCAS RACINES, DANIEL ALEJANDRO; ZAMBRANO ESPINOSA, ANA KARINA (Informa UK Limited, 2024)
Neurodegenerative diseases (NDDs) affect millions of lives worldwide. They constitute a group of neurological disorders with shared common features, including impaired cognition, behavior, memory, and motor functions. These conditions arise due to the gradual degeneration of neurons within the nervous system. Even though, each pathology presents diverse etiologies and develops in different brain sites, they may share cellular and molecular mechanisms, such as inflammation, protein aggregation, and DNA and RNA defects. Heavy metal contamination is a global public health concern, given that anthropogenic activities like paint manufacturing, mining, and oil refining contribute substantially to heavy metal pollution. Consequently, studies have investigated its potential etiological factors in neurodegenerative diseases. This review examines the impact of dietary exposure to heavy metals, specifically mercury, cadmium, lead, chromium, arsenic, and zinc, on the development and progression of neurodegenerative diseases. Evidence from a range of studies indicates that these metals play a significant role in advancing these diseases by disrupting essential cellular and molecular functions, including the induction of oxidative stress and impairments in mitochondrial function. These findings underscore the need for further research to elucidate toxicological mechanisms and develop preventive strategies, such as chelation therapies and environmental remediation. Addressing these risks is especially critical to protect neurocognitive health, particularly in aging populations.
Keywords: contamination; diet; Heavy metals; neurodegeneration